2021
DOI: 10.1016/j.lfs.2021.119201
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19, cytokines, inflammation, and spices: How are they related?

Abstract: Background Cytokine storm is the exaggerated immune response often observed in viral infections. It is also intimately linked with the progression of COVID-19 disease as well as associated complications and mortality. Therefore, targeting the cytokine storm might help in reducing COVID-19-associated health complications. The number of COVID-associated deaths (as of January 15, 2021; https://www.worldometers.info/coronavirus/ ) in the USA is high (1199/million) as compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
91
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(96 citation statements)
references
References 470 publications
(344 reference statements)
2
91
0
3
Order By: Relevance
“…It has been reported that oxidative stress plays an important role in the pathogenesis of various diseases [11] , [12] , [14] , [19] . Many studıes showed that the levels of parameters such as MDA, IL-1B and TNF-alpha associated with oxidative stress in various viral diseases were high compared to the control group while the levels of antioxidan parameters such as GSH, SOD, CAT and GSH-Px were low [24] , [25] . Because the measurement of antioxidant-oxidant parameters is a manual process, it is a costly and time consuming endeavor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that oxidative stress plays an important role in the pathogenesis of various diseases [11] , [12] , [14] , [19] . Many studıes showed that the levels of parameters such as MDA, IL-1B and TNF-alpha associated with oxidative stress in various viral diseases were high compared to the control group while the levels of antioxidan parameters such as GSH, SOD, CAT and GSH-Px were low [24] , [25] . Because the measurement of antioxidant-oxidant parameters is a manual process, it is a costly and time consuming endeavor.…”
Section: Discussionmentioning
confidence: 99%
“…CRP, Ferritin and D-Dimer parameters among routine biochemistry parameters are especially used as determinants in the prognosis of in Covid 19 [1] . In many studies, it was stated that patients infected with COVID-19 started to increase in proinflammatory cytokines such as TNF-α and IL-1β and oxidants such as lipid peroxidation, disulfide level and oxidative DNA damage [24] , [25] , [26] . In these studies, it was also stated that patients infected with COVID-19 started to decrease in antioxidants such as superoxide dismutase (SOD), glutathione (GSH), glutathione peroxidase (GPx), total thiol, and native thiol [24] , [25] , [26] .…”
Section: Introductıonmentioning
confidence: 99%
“…The pathophysiologic mechanisms of COVID-19 are not yet well understood. However, clinical studies have suggested that patients infected with COVID-19 often show increased levels in cytokines, termed ‘cytokine storm’ ( Lordan et al, 2021 , Kunnumakkara et al, 2021 ). This abnormal level of cytokines occurs together with severe deterioration of health in infected patients ( Ye et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…In a very recent systematic review, Kunnumakkara et. al., explained the potential of curcumin and other spices against SARS-COV-2 due to their anti-inflammatory properties to inhibit the cytokine storm [70]. These findings suggest that turmeric extracts not only could be a potential treatment but also a prevention alternative for viral infections.…”
Section: Antiviralmentioning
confidence: 89%